Summaries of Judgments, Advisory Opinions and Orders of the International Court of Justice 1948-1991 - United Nations (United Nations, 1992)
In an effort to make international law and United Nations legal activities more accessible, this publication condenses chronologically in a single and handy volume the case-law of the International Court of Justice for the period 1948-1991. Lawyers, journalists, diplomats, specialists in international law will greatly profit from these summaries based closely on the texts prepared by the Registry of the Court.